The Compatible Solute Ectoine Reduces the Exacerbating Effect of Environmental Model Particles on the Immune Response of the Airways. (12th April 2014) - Unfried, Klaus; Kroker, Matthias; Autengruber, Andrea; Gotić, Marijan; Sydlik, Ulrich
Abstract : Exposure of humans to particulate air pollution has been correlated with the incidence and aggravation of allergic airway diseases. In predisposed individuals, inhalation of environmental particles can lead to an exacerbation of immune responses. Previous studies demonstrated a beneficial effect of the compatible solute ectoine on lung inflammation in rats exposed to carbon nanoparticles (CNP) as a model of environmental particle exposure. In the current study we investigated the effect of such a treatment on airway inflammation in a mouse allergy model. Ectoine in nonsensitized animals significantly reduced the neutrophilic lung inflammation after CNP exposure. This effect was accompanied by a reduction of inflammatory factors in the bronchoalveolar lavage. Reduced IL-6 levels in the serum also indicate the effects of ectoine on systemic inflammation. In sensitized animals, an aggravation of the immune response was observed when animals were exposed to CNP prior to antigen provocation. The coadministration of ectoine together with the particles significantly reduced this exacerbation. The data indicate the role of neutrophilic lung inflammation in the exacerbation of allergic airway responses. Moreover, the data suggest to use ectoine as a preventive treatment to avoid the exacerbation of allergic airway responses induced by environmental air pollution.